An Analysis of Mathematics Anxiety Among Prospective Mathematics Teachers in Discrete Mathematics Courses - Prasetyo, Agung; Kurniawati, Endang (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
Anxiety is one of the affective factors that can influence success in learning mathematics. Many studies have shown that the majority of students experience high levels of mathematics anxiety, and this condition can even be transferred to future mathematics teachers. This study aims to describe the mathematics anxiety of prospective mathematics teachers during discrete mathematics lectures. The research employed a descriptive quantitative method. The instrument used was an anxiety questionnaire, administered using a Likert scale. In addition, several open-ended questions were included to further describe the anxiety profile and support the quantitative data. The study involved 29 students from the Mathematics Department of the Ponorogo Islamic Institute of Religion. The results revealed that the majority (93.1%) of students experienced moderate levels of mathematics anxiety, while a small proportion (3.45%) experienced low or high anxiety. Based on the dimensional analysis, mathematics anxiety across the cognitive, psychological, and physiological dimensions was mostly categorized as moderate. However, in the physiological dimension, a considerable number of students (44.44%) reported low anxiety. The findings imply that lecturers should continue to develop innovative teaching strategies to help reduce students’ mathematics anxiety.